Factors influencing circular economy implementation in smes business models: the case of Spain - Cano-Rubio, Myriam; Maglio, Roberto; Núñez-Cacho Utrilla, Pedro (Piccola Impresa / Small Business, 2021)
Nowadays, Europe has to add more value to the resources it uses and make all sectors more productive, so the transition to a circular economy (CE) requires a stronger link between waste reduction and resource efficiency. Small and medium-sized enterprises are increasingly aware of the benefits of closing loops and improving resource efficiency, creating competitive advantages, and accessing new markets. In the learning of valuing waste as a resource and apply the lessons of the natural world, in which nothing is wasted, SMEs embraces the CE to achieve sustainability. In this line, the agro-food system plays an important role since it needs that agricultural practices aim at optimising yields and improving the natural resources, what is crucial for embracing CE. We conclude by using mixed methodology, where 161 SMEs took part that they characterise by the inappropriate lack of technical and technological resources, even though they consider innovation crucial to achieve a competitive advantage. Therefore, the EU policies, in general, and the Spanish ones, in particular, should reinforce the “Green Economy” and help SMEs, incorporate CE principles into their business models.